Interaction of the Cytosolic Domains of sorLA/LR11 with the Amyloid Precursor Protein (APP) and β-Secretase β-Site APP-Cleaving Enzyme - Spoelgen, Robert (J Neurosci, 2006)
sorLA is a recently identified neuronal receptor for amyloid precursor protein (APP) that is known to interact with APP and affect its intracellular transport and processing. Decreased levels of sorLA in the brain of Alzheimer's disease (AD) patients and elevated levels of amyloid-β peptide (Aβ) in sorLA-deficient mice point to the importance of the receptor in this neurodegenerative disorder. We analyzed APP cleavage in an APP-shedding assay and found that both sorLA and, surprisingly, a sorLA tail construct inhibited APP cleavage in a β-site APP-cleaving enzyme (BACE)-dependent manner. In line with this finding, sorLA and the sorLA tail significantly reduced secreted Aβ levels when BACE was overexpressed, suggesting that sorLA influencesβ-cleavage. To understand the effect of sorLA on APP cleavage by BACE, we analyzed whether sorLA interacts with APP and/or BACE. Because both full-length sorLA and sorLA C-terminal tail constructs were functionally relevant for APP processing, we analyzed sorLA–APP for a potential cytoplasmatic interaction domain. sorLA and C99 coimmunoprecipitated, pointing toward the existence of a new cytoplasmatic interaction site between sorLA and APP. Moreover, sorLA and BACE also coimmunoprecipitate. Thus, sorLA interacts both with BACE and APP and might therefore directly affect BACE–APP complex formation. To test whether sorLA impacts BACE–APP interactions, we used a fluorescence resonance energy transfer assay to evaluate BACE–APP interactions in cells. We discovered that sorLA significantly reduced BACE–APP interactions in Golgi. We postulate that sorLA acts as a trafficking receptor that prevents BACE–APP interactions and hence BACE cleavage of APP.